2019
DOI: 10.31234/osf.io/zfxj2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure Learning and the Parietal Cortex

Abstract: We propose a theory of structure learning in the primate brain. We argue that the parietal cortex is critical for learning about relations among the objects and categories that populate a visual scene. We suggest that current deep learning models exhibit poor global scene understanding because they fail to perform the relational inferences that occur in the primate dorsal stream. We review studies of neural coding in primate posterior parietal cortex (PPC), drawing the conclusion that this brain area represent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…Based on this property of the task, we can hypothesise a cognitive mechanism that could generate our above results, as follows. Summerfield et al (2019) recently described a theory for the role of posterior parietal cortex (PPC, i.e. part of the dorsal visual stream, the so-called 'what' stream) in processing relational structure in the environment.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…Based on this property of the task, we can hypothesise a cognitive mechanism that could generate our above results, as follows. Summerfield et al (2019) recently described a theory for the role of posterior parietal cortex (PPC, i.e. part of the dorsal visual stream, the so-called 'what' stream) in processing relational structure in the environment.…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
“…It is possible that revaluation choices changed these cached CS values, instead of the CS-US associations. Under this reasoning, one would assume that the value information conveyed by CS 0 A, the CS not chosen during revaluation and supposedly devalued, would become more similar to the value information of the low-valued USafter choice-induced revaluation (Summerfield, Luyckx, & Sheahan, 2019 However, as we did not find behavioral support for the hypothesized devaluation effect, the "cached value" effects should be interpreted with caution.…”
Section: Hippocampal Cs-us Repetition Suppression Correlates With Futmentioning
confidence: 68%
“…We showed that the ADHD group showed lower theta synchronisation during correct inhibition trials, and demonstrated reduced sensitivity to stimulus timing across several parietal measures. The interpretation of these results is noteworthy, as it points to deficient attention sampling in relational categorisation tasks (75). This result contributes to the overall understanding of the neuropathology of ADHD in adults.…”
Section: Resultsmentioning
confidence: 88%
“…Summerfield et al (75) recently described a theory for the role of posterior parietal cortex (PPC, i.e. the dorsal visual stream, or the ‘what’ stream) in processing relational structure in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation